Contextualization of Communicative Language Teaching in Confucian Heritage Culture: Challenging Pedagogic Dichotomization. (March 2022) - Han, Insuk
Based on the comprehensive comparison of the principles of communicative language teaching (CLT) and the pedagogic ideas of Confucian heritage culture (CHC), this study discusses the conceptual common ground, where both principles can be reconciled, and considers practical, negotiated pedagogic forms with the suggestion of some cases of contextualization of CLT in CHC. In summary, CLT and CHC can be reconciled in their pursuit of education for the whole person, cooperative learning, teaching language structures and content, and task completion orientation. Thus, by distributing more responsibilities to learners and encouraging their participation, students in CHC can experience more communicative lessons. By balancing teaching language forms and content, they can learn language in a more comprehensive way, and by applying task-based learning with precise procedures and controls, their task-orientation tendency can enable students to participate in more communicative activities. These comprehensions and discussions, as a challenge to pedagogic dichotomization, will help English teachers in CHC or intercultural classrooms to flexibly construct context-sensitive pedagogies.